Analysis of the Impacts of Dam Construction on Water Quality and the Surrounding Ecosystem of the Pamukkulu Dam, Takalar Regency - Fajar N. Utomo; Syafrudin; Anik Sarminingsih (Jurnal Penelitian Pendidikan IPA, 2025)
Dam construction offers substantial benefits to society, including the raw water supply. However, such projects also exert significant impacts on water quality and the surrounding ecosystems. This study aims to examine changes in water quality and their subsequent effects on the local ecosystem, as well as to propose appropriate mitigation strategies. The methodology employed includes the measurement of physico-chemical water parameters and biodiversity surveys. A case study was conducted at the Pamukkulu Dam by comparing water quality conditions at two sites (the upstream and downstream) before and after construction. The findings reveal a deterioration in water quality attributable to sediment accumulation, eutrophication, and alterations to natural habitats and local biodiversity within one year following impoundment. Notably, BOD levels downstream increased from 1.07 mg/L to 6.18 mg/L, while COD levels rose from 7.04 mg/L to 105.68 mg/L. Ammonia concentrations downstream increased from <0.001 mg/L to 1.09 mg/L, and total coliform counts escalated from 11 MPN/100 mL to 2,800 MPN/100 mL. Furthermore, oil and fat levels downstream rose from <0.02 mg/L to 0.19 mg/L, and MBAS levels increased from <0.01 mg/L to 0.01 mg/L. This study concludes that dam construction significantly affects water quality and ecosystems, particularly within the reservoir and downstream river areas.